The small things of Global South: Exploring the use of social media through translingualism. (February 2023) - Dryden, Stephanie; Izadi, Dariush
Abstract: In this paper, we present a research approach that sheds light on how netizens on social media perform and negotiate their multimodal and multisemiotic repertoires embedded within their social media languaging practices. This approach brings multimodal social semiotics into conversation with the normativity of translingualism to problematise the notion of languages as being 'ordinary' or 'mundane', and to illustrate how translingual netizens deploy their knowledge of the features of different language scripts, modalities and 'small things' (e.g., the use of emojis, replies, and comments) to increase and exploit their communicative capacity. In order to explore this claim, drawing upon digital ethnography approaches as our guiding methodology, the study investigates a YouTube post and responding comments from Global South settings. We illustrate that the subtext of their translingual practices is influenced by how they move beyond discourses and ideologies from the Global North. The analysis will consider the nature of communication in the aforementioned online communities from historical and contemporary perspectives, focusing on how our participants exploit local linguistic diversity as a resource and on how they extract a piece of text or discourse from its original context and bring it to a new context (i.e., online) and modify this material so that it fits into the new context. This article, therefore, contributes to the emerging body of work on the normativity of translingualism in communities around the world.